Sailing a beginner's guide - Seidman, David (Adlard Coles Nautical, 2007)
This step-by-step guide takes the reader from his or her first sail to an almost intuitive mastery of small boat handling. The author's text is supported by drawings to explain topics such as reading the wind, navigation, safety aboard, and seamanship.